2019
DOI: 10.9734/air/2019/v18i530100
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Sequestration Potential and Economic Value in Agroforestry Parkland to Tectona grandis L. f. (Verbenaceae) in Central Africa: A Case Study to Department of Poli (Northern Region in Cameroon)

Abstract: The vegetation and the afforestation of agricultural land non-forest represent a potential increase in carbon stocks which could, under certain conditions and within certain limits, compensate part of the emissions resulting from the use of fossil fuels and deforestations. Quantification of stocks of biomass and carbon dioxide contained in agroforestry systems has become an international priority within the framework of the implementation of REDD+ mechanism. Estimates of stocks of carbon in woody biomass, dead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(26 reference statements)
2
2
0
Order By: Relevance
“…This is consistent with the findings ofSiriki et al (2022) who concluded that the amount of carbon sequestered in agroforestry systems is linked to the circumference of trees which is linked to the diameter. This is in line withVictor et al (2019) who reported that more a tree has a large circumference, more he occupies an important basal area and receive a large quantity of carbon. In addition to this,Wafa et al (2016) showed that trees in drylands can increase biomass carbon stocks.The tree species are promoted and protected by local communities through natural regeneration in the agroecological zones in Maradi Region.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the findings ofSiriki et al (2022) who concluded that the amount of carbon sequestered in agroforestry systems is linked to the circumference of trees which is linked to the diameter. This is in line withVictor et al (2019) who reported that more a tree has a large circumference, more he occupies an important basal area and receive a large quantity of carbon. In addition to this,Wafa et al (2016) showed that trees in drylands can increase biomass carbon stocks.The tree species are promoted and protected by local communities through natural regeneration in the agroecological zones in Maradi Region.…”
supporting
confidence: 90%
“…In addition to this,Wafa et al (2016) showed that trees in drylands can increase biomass carbon stocks.The tree species are promoted and protected by local communities through natural regeneration in the agroecological zones in Maradi Region. These results corroborate those found bySiriki et al (2022) who reported that, the rate of carbon sequestered by agroforestry systems depends on the maintenance techniques of these systems in Dioïla Région(Mali Republic).Thereby, good practices represent a potential increase in carbon sequestration and fight against climate change through carbon storage(Victor et al, 2019;Mensah et al, 2020;Elvire et al, 2023) through the presence of trees in agricultural system. These systems with good practices play an important role through…”
supporting
confidence: 88%
“…This organic matter generally comes from dead, mainly plant organs and organisms, animal excreta, root exudates and living organisms (Gorham et al, 2020). The organic matter (OM) then undergoes biotransformation in the soil : biodegradation and finally mineralization, which returns the Carbon to the atmosphere in the form of CO2 (Awé et al, 2019a). Carbon exchanges between the atmosphere and terrestrial ecosystems are about ten times greater than the emissions caused by the use of fossil fuels (FAO, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the terrestrial ecosystem, carbon sequestration is achieved by photosynthesis, which eliminates carbon from the environment and deposits in the biosphere [5,6]. Biomass is considered a vital carbon reservoir in the terrestrial ecosystem, thus playing a crucial role in the global carbon cycle [7].…”
Section: Introductionmentioning
confidence: 99%